Analisis Kualitas Pelayanan Pemerintah Desa Sumber Harum Kecamatan Tungkal Jaya - Lilis Purwaningsih; Novita Sari; Ade Perdana Siregar (Politeknik Kampar, 2026)
This study aims to analyze the quality of public services in Sumber Harum Village Government based on service standards and the SERVQUAL indicators, and to identify the factors that affect the quality of these services. The method used is a qualitative approach with in-depth interviews conducted with five community members who receive the services and two village officials who provide them. The results show that village administrative services are running fairly well, especially in terms of service product accuracy, the friendliness of the staff, and the speed of handling simple documents. However, there are still some challenges, such as the lack of written SOPs, technical issues caused by unstable electricity and signal, facilities that are not fully suitable for the elderly, and unofficial fees for certain types of services. According to the SERVQUAL analysis, service quality is considered good in the dimensions of reliability, assurance, and empathy, but still needs improvement in the dimensions of physical evidence and responsiveness. Overall, public services in Sumber Harum Village meet some of the principles of good service, but still require improvements in transparency, service consistency, and the provision of supporting facilities to make the services more effective and responsive to community needs.